Ambiguous boundaries between exclusion and inclusion. Experiences from the Meheba Refugee Camp (Zambia) - Neto, Pedro Figueiredo (2018)
Refugee camps are often created and portrayed as places of exclusion where “supernumerary” (Bauman 2004), “undesired populations” (Agier 2011) are concentrated. And yet, experiences from the Meheba Refugee Settlement show that the reality is rather more complex, providing evidence of the ambiguous line between inclusion and exclusion involving refugees and the neighbouring population.